Ketogenic diets: from cancer to mitochondrial diseases and beyond. (March 2016) - Branco, Ana F.; Ferreira, André; Simões, Rui F.; Magalhães‐Novais, Sílvia; Zehowski, Cheryl; Cope, Elisabeth; Silva, Ana Marta; Pereira, Daniela; Sardão, Vilma A.; Cunha‐Oliveira, Teresa
Abstract: Background: The employment of dietary strategies such as ketogenic diets, which force cells to alter their energy source, has shown efficacy in the treatment of several diseases. Ketogenic diets are composed of high fat, moderate protein and low carbohydrates, which favour mitochondrial respiration rather than glycolysis for energy metabolism. Design: This review focuses on how oncological, neurological and mitochondrial disorders have been targeted by ketogenic diets, their metabolic effects, and the possible mechanisms of action on mitochondrial energy homeostasis. The beneficial and adverse effects of the ketogenic diets are also highlighted. Results and conclusions: Although the full mechanism by which ketogenic diets improve oncological and neurological conditions still remains to be elucidated, their clinical efficacy has attracted many new followers, and ketogenic diets can be a good option as a co‐adjuvant therapy, depending on the situation and the extent of the disease.